ANALISIS KESESUAIAN ILUSTRASI BUKU TEKS SEJARAH KEBUDAYAAN ISLAM K13 MTs KELAS 9 TERBITAN KEMENAG - Gusti Katon (At-Tarbiyat, 2020)
This study aims to provide an overview of the results of the analysis of the suitability of the illustrations. In the analysis results of the illustrations listed at the beginning of the chapter, namely the beginning of chapters II-XIV are not appropriate, the discrepancy is because the illustrations listed do not match the chapter title, the scope of this study is SKI textbooks for grade 9 MTs students published by the Ministry of Religion. This study is important because illustrations that fit 11 standard dance perspectives can add to the attractiveness of a reader. This research is a library research using library analysis, which is done through collecting data, compiling or classifying it, and then interpreting the data, results from this study the SKI textbook for 9th grade MTs students published by the Ministry of Religion still needs improvement. According to the analysis, the illustrations at the beginning of the chapter (chapters II-XIV) with the chapter titles are not appropriate. The illustrations listed do not match the material to be conveyed, so there is a need for revisions to the 9th grade SKI textbook illustrations and the need for additional illustrations.